Ludwig Erhard : a biography - Mierzejewski, Alfred C. (University of North Carolina Press, 2004)
"In the first English language biography of one of the most important figures in postwar German history, Alfred C. Mierzejewski examines the life and service of Ludwig Erhard (1897-1977), West Germany's first minister of economics and second chancellor. Erhard liberalized the German economy in 1948 and is generally considered the father of West Germany's "economic miracle"--The period of extraordinary growth in jobs and improvement in the standard of living in the 1950s that helped stabilize Germany's first successful democracy." "While recent scholarship has dismissed Erhard's influence on Germany's economic recovery. Mierzejewski returns to little cited German analyses and Erhard's own record and concludes, that Allied currency reform and Erhard's liberalization of the economy were critical triggers for Germany's unprecedented economic boom in addition to evaluating Erhard's major policies, Mierzejewski also details the less well known aspects of Erhard's leadership, such as his struggle against cartels and the Common Market, his effort to arrest the growth of the welfare state, his battle for free trade and his consistent efforts to cut taxes."--Jacket.